Um indivíduo com Sídrome de Asperger: estudo de caso a partir de análise das produções de atividades expressivas pelas trilhas associativas - Hernandes, Raphaela Schiassi (2010)
The current work, with focus on a study case of a bearer of Asperger Syndrome, aimed to verify the possibility to gather information from history and development of a patient with Asperger Syndrome, through the technique of analysis of activities from Dynamic Occupational Therapy Method associative trails. For that, it was fixed as specific goals: a) to verify whether it is possible to happen associations and some historical narrative of the patient s development, through the activities done by himself; b) to analyse whether the associative trails can be a tool for qualitative research on Occupational Therapy; c) to verify the possibility of applying the technique - associative trails as an intervention tool in medical clinic, with Asperger Syndrome patients. By using a technique of analysis of associative trails from Dynamic Occupational Therapy Method four meeting were held with the patient lasting one hour and a half each meeting. Activities were photographed to review them at the last meeting and guide the analysis of them as well. It was possible to use this tool to research the situation of the patient and collect data about: 1) situational diagnosis, 2) levels of interaction, 3) performance of activities and 4) establishment of procedure to assist in occupational therapy. The results showed that besides making associations for the analysis of activities, the patient also completed the narrative begun by the research. The associative trail tool allowed having a situational diagnosis of the patient, demonstrating how he was, facing the therapist and his own accomplished activities. It was also possible to evaluate that in this specific case the associative trail technique could be used to assist him. To be truly approved this work it must be applied this tool in more subject, which is really intended by the researcher in a broader research.